Underwater super-oleophobic alumina ceramic microfiltration membrane and preparation method and application thereof
By adding nanosilicon dioxide to the alumina ceramic membrane and adjusting the sintering process, an alumina ceramic microfiltration membrane with small pore size and large porosity was prepared, which solved the problem of reduced flux and unresisting oil pollution in the filtration of emulsified oil, and achieved efficient oil-water separation and pure water treatment effects.
Patent Information
- Application Number
- CN202411769185.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
AI Technical Summary
The existing alumina ceramic membranes are easily blocked by oil droplets during the emulsified oil filtration process, resulting in a decrease in membrane flux and are not resistant to oil pollution, and have limited demulsification effect.
By treating nano-alumina and nano-silicon dioxide ball milling, adding binder and pore forming agent, an alumina ceramic microfiltration membrane with small pore size and large porosity is prepared, and the membrane pore size is controlled to improve the emulsification ability by adjusting the liquid phase generation during the sintering process.
The obtained underwater superoleophobic alumina ceramic microfiltration membrane has high purity water flux and good petroleum ether retention properties, which can effectively prevent oil droplet adhesion, improve anti-pollution ability, reduce transmembrane pressure difference, and save energy.
Smart Images

Figure CN119588178A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an underwater super oleophobic alumina ceramic microfiltration membrane and a preparation method and application thereof, belonging to the technical field of inorganic ceramic microfiltration membranes and preparation thereof. Background Art
[0002] A large amount of oily wastewater is generated in industrial production and daily life, posing a major threat to ecological security. Emulsified oil usually exists stably in water bodies with a particle size of 0.1μm-20μm. Existing conventional water purification processes such as gravity separation, coagulation, adsorption, and flotation have limited effects on emulsified oil treatment and are difficult to treat. Membrane technology has the advantages of simple operation and environmental friendliness, and is an efficient method for treating oily wastewater.
[0003] Polymer membranes dominate water treatment due to their ease of processing and low preparation cost. However, polymer membranes have poor chemical resistance and short service life. In contrast, ceramic membranes have good mechanical properties, excellent thermal stability and chemical stability. These advantages prove the feasibility of ceramic membranes in industrial water treatment, especially in emulsified oil separation.
[0004] Alumina has high hardness, stable chemical properties and low cost, and has the potential to become the main raw material for water treatment ceramic membranes. Existing alumina ceramic membranes have large sintered pores and poor oleophobicity. During the emulsified oil filtration process, the surface of the ceramic membrane is easily adsorbed and blocked by oil droplets, resulting in reduced membrane flux. Therefore, it is very necessary to provide a method that can effectively adjust the membrane pore size to improve the demulsification effect and improve the underwater oleophobicity of the alumina ceramic membrane to control membrane pollution. Summary of the invention
[0005] In view of the problem that existing alumina ceramic membranes are not resistant to oil pollution, the present invention provides an underwater super oleophobic alumina ceramic microfiltration membrane and a preparation method and application thereof.
[0006] The technical solution of the present invention:
[0007] One of the purposes of the present invention is to provide a method for preparing an underwater super oleophobic alumina ceramic microfiltration membrane, the specific method comprising the following steps:
[0008] (1) ball-milling nano-alumina, nano-silicon dioxide and water to obtain a powder dispersion;
[0009] (2) adding a binder and a pore-forming agent to the powder dispersion for secondary ball milling, fully mixing, drying, and sieving to obtain a pre-pressed powder;
[0010] (3) placing the pre-pressed powder in a mold and pressing it into shape to obtain a ceramic green body membrane;
[0011] (4) Sintering the ceramic green body membrane to obtain an underwater super oleophobic alumina ceramic microfiltration membrane.
[0012] It is further defined that in (1), the particle size of nano-alumina is 150-300 nm, the particle size of nano-silicon dioxide is 30-200 nm; and the molar ratio of nano-alumina to nano-silicon dioxide is 1:0.05-3.
[0013] It is further defined that the ball milling treatment time in (1) is 12 to 48 hours.
[0014] It is further defined that the binder in (2) is a mixture of one or more of methyl cellulose, carboxymethyl cellulose and polyvinyl alcohol.
[0015] It is further defined that the amount of the binder added is 1 to 20% of the mass of the pre-pressed powder.
[0016] It is further defined that (2) the pore-forming agent is a mixture of one or more of corn starch, calcium carbonate and yellow dextrin.
[0017] It is further defined that the amount of the pore former added is 5 to 70% of the mass of the pre-pressed powder.
[0018] It is further defined that the pressure of the compression molding in (3) is 5 to 60 MPa.
[0019] It is further defined that the thickness of the ceramic green body membrane obtained in (3) is 0.5 to 2.5 mm.
[0020] It is further defined that the sintering conditions in (4) are: raising the temperature from room temperature to 200°C at a rate of 0.5-5°C / min, keeping it at that temperature for 0.5-3h, then raising the temperature to 800°C at a rate of 0.5-15°C / min, keeping it at that temperature for 0.5-3h, and finally raising the temperature to 1100-1600°C at a rate of 0.5-15°C / min, keeping it at that temperature for 0.5-10h.
[0021] The second object of the present invention is to provide an underwater super oleophobic alumina ceramic microfiltration membrane prepared by the above method.
[0022] The third object of the present invention is to provide an application of the above-mentioned underwater super oleophobic alumina ceramic microfiltration membrane, specifically for use in the technical fields of oil-water separation, wastewater treatment and drinking water treatment.
[0023] Beneficial effects:
[0024] The invention adds nano silicon dioxide to the alumina ceramic sintering system, utilizes silicon dioxide to generate liquid phase during the sintering process, wets the surface of alumina crystal grains under the action of capillary force, activates the crystal lattice, and achieves the purpose of regulating the membrane pore size by adjusting the amount of liquid phase generated during the sintering process. The alumina ceramic microfiltration membrane with small pore size and large porosity is obtained, which has good demulsification ability and the interception performance of petroleum ether reaches more than 90%. At the same time, it has a high pure water flux. Taking the 1200°C sintered membrane as an example, the pure water flux can reach 1300L·m -2 ·h -1 bar -1 . The obtained alumina ceramic microfiltration membrane has underwater super oleophobicity (the underwater oil contact angle is greater than 150°), which can effectively prevent oil droplets from adhering to the surface of the ceramic membrane in the treatment of oily wastewater and industrial oil-water separation, improve the anti-pollution ability of the ceramic membrane during operation, reduce the trans-membrane pressure difference during the filtration process, and save energy. The alumina ceramic microfiltration membrane is hydrophilic. In drinking water treatment, it can effectively remove large particulate matter in the water body and protect the effective operation of subsequent water treatment processes. In addition, the preparation method of the alumina ceramic microfiltration membrane provided by the present invention can adjust the membrane pores by adjusting the molar ratio of alumina to silica according to demand, and has the characteristics of flexible operation mode, simple operation method, and low raw material price. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM photo of the alumina ceramic membrane prepared in Example 1;
[0026] Figure 2 This is a SEM photo of the alumina ceramic membrane prepared in Example 2;
[0027] Figure 3 This is a SEM photo of the alumina ceramic membrane prepared in Example 3;
[0028] Figure 4 This is a pore size distribution diagram of the alumina ceramic membrane prepared in Example 1;
[0029] Figure 5 This is the pore size distribution diagram of the alumina ceramic membrane prepared in Example 2;
[0030] Figure 6 This is the pore size distribution diagram of the alumina ceramic membrane prepared in Example 3;
[0031] Figure 7 This is a comparison of the underwater oil contact angles of alumina ceramic membranes with different molar ratios of alumina and silica. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0033] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0034] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0035] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.
[0036] Example 1
[0037] The process of preparing the alumina ceramic membrane in this embodiment is as follows:
[0038] (1) Add 150 mL of water to a ball mill, add 3.1 g of alumina with a particle size of 200 nm and 1.5 g of silica with a particle size of 50 nm (the molar ratio of alumina to silica is 1:0.1) to the ball mill, and mix thoroughly for 12 h to obtain a uniform powder dispersion;
[0039] (2) adding 0.1 g of polyvinyl alcohol and 2 g of corn starch to the dispersion, and ball milling and mixing again for 12 h. After the powder is fully mixed, it is placed in a vacuum drying oven at 80 °C and passed through a 325 mesh sieve;
[0040] (3) placing the dried powder in a dry pressing mold and biaxially pressing it into a film with a thickness of 1.5 mm at a pressure of 20 MPa;
[0041] (4) The ceramic body is placed in a tubular furnace, heated to 200°C at a heating rate of 1.5°C / min, and kept at this temperature for 1 hour; then heated to 800°C at a heating rate of 1.5°C / min and kept at this temperature for 1 hour; then heated to 1200°C at a heating rate of 2°C / min, sintered for 5 hours, and cooled naturally to obtain an alumina ceramic film.
[0042] The obtained alumina ceramic membrane was subjected to dead-end filtration to test the membrane flux and petroleum ether retention rate. The specific test process was to place the ceramic membrane with its front side facing up at the bottom of the ultrafiltration cup, and the oil emulsion to be filtered was placed on the upper part of the ceramic membrane. The test was carried out under pressure, and the produced water was produced from the bottom of the ultrafiltration cup. The filtration volume of each test cycle was 150 mL, and the pressure required for filtration was provided by a nitrogen bottle. During the experiment, the transmembrane pressure difference was constant at 0.1 MPa, and the water production was recorded every 4 seconds by an electronic balance and collected through an information acquisition system. The specific test results are as follows: the pure water flux of the alumina ceramic membrane is 974.93 L·m -2 ·h -1 bar -1 The retention rate of petroleum ether is 96%.
[0043] Example 2
[0044] The process of preparing the alumina ceramic membrane in this embodiment is as follows:
[0045] (1) Add 150 mL of water to a ball mill, add 7.6 g of alumina with a particle size of 200 nm and 4 g of silica with a particle size of 50 nm (the molar ratio of alumina to silica is 1:0.4) to the ball mill, and mix thoroughly by ball milling for 8 h to obtain a uniform powder dispersion;
[0046] (2) adding 0.3 g of polyvinyl alcohol and 2 g of corn starch to the dispersion, and ball milling was performed again for 12 h. After the powder was fully mixed, it was dried in a vacuum drying oven at 80 °C and passed through a 325 mesh sieve;
[0047] (3) placing the dried powder in a dry pressing mold and biaxially pressing it into a 2 mm thick film at a pressure of 30 MPa;
[0048] (4) The ceramic body is placed in a tubular furnace, heated to 200°C at a heating rate of 0.5°C / min, and kept at this temperature for 1 hour; then heated to 800°C at a heating rate of 1.5°C / min for 1 hour; then heated to 1200°C at a heating rate of 2°C / min, sintered for 5 hours, and cooled naturally to obtain an alumina ceramic film.
[0049] The obtained alumina ceramic membrane was tested for membrane flux and petroleum ether retention rate by dead-end filtration. The test results showed that the pure water flux of the alumina ceramic membrane was 1319.44 L·m -2 ·h -1 bar -1 The retention rate of petroleum ether is 97%.
[0050] Example 3
[0051] The process of preparing the alumina ceramic membrane in this embodiment is as follows:
[0052] (1) Add 150 mL of water to a ball mill, add 3.5 g of alumina with a particle size of 200 nm and 2 g of silica with a particle size of 50 nm (the molar ratio of alumina to silica is 1:0.8) to the ball mill, and mix thoroughly by ball milling for 8 h to obtain a uniform powder dispersion;
[0053] (2) Add 0.5 g of polyvinyl alcohol and 3 g of corn starch to the dispersion, and mix again with ball mill for 12 h. After the powder is fully mixed, place it in a vacuum drying oven at 80 °C and pass it through a 325 mesh sieve;
[0054] (3) placing the dried powder in a dry pressing mold and biaxially pressing it into a 2 mm thick film at a pressure of 40 MPa;
[0055] (4) The ceramic body is placed in a tubular furnace, heated to 200°C at a heating rate of 1.5°C / min, and kept at this temperature for 1 hour; then heated to 800°C at a heating rate of 1.5°C / min and kept at this temperature for 1 hour; then heated to 1300°C at a heating rate of 2°C / min, sintered for 5 hours, and cooled naturally to obtain an alumina ceramic film.
[0056] The obtained alumina ceramic membrane was tested for membrane flux and petroleum ether retention rate by dead-end filtration. The test results showed that the pure water flux of the alumina ceramic membrane was 1266.31 L·m -2 ·h -1 bar -1 The retention rate of petroleum ether is 93%.
[0057] The surface microstructures of the alumina ceramic films obtained in Examples 1 to 3 were characterized, and the SEM photos were as follows: Figures 1 to 3 As shown in the figure, it can be seen that the prepared alumina ceramic membrane has the characteristics of small pore size and large porosity, and the pore size and porosity change with the change of the molar ratio of alumina to silicon dioxide. Further, the pore size distribution of the alumina ceramic membrane obtained according to Examples 1 to 3 (respectively as Figures 4 to 6 ) It can be seen that when the molar ratio of alumina to silica is high, the distance between alumina particles is large, the membrane pores are large, and the demulsification ability is weak; when the molar ratio is low, more liquid phase is generated, the distance between particles becomes smaller, the membrane pore size decreases, and the demulsification ability is strong. When the molar ratio of alumina to silica is 1:0.4, the pore size is mainly distributed around 236nm. At this time, the alumina ceramic membrane has a higher pure water flux and a higher retention rate for petroleum ether.
[0058] Comparative Example 1
[0059] The difference between this embodiment and embodiment 1 is that the amount of silicon dioxide added is 0, and the remaining process steps and parameter settings are the same as those in embodiment 1, to obtain an alumina ceramic film.
[0060] Example 4
[0061] The difference between this embodiment and embodiment 1 is that the molar ratio of aluminum oxide to silicon dioxide is 1:0.2, and the remaining process steps and parameter settings are the same as those in embodiment 1, to obtain an aluminum oxide ceramic film.
[0062] Example 5
[0063] The difference between this embodiment and embodiment 1 is that the molar ratio of aluminum oxide to silicon dioxide is 1:0.6, and the remaining process steps and parameter settings are the same as those in embodiment 1, to obtain an aluminum oxide ceramic film.
[0064] The underwater oil contact angle of the alumina ceramic membranes obtained in Examples 1 to 5 and Comparative Example 1 was tested. The results are as follows: Figure 7 As shown by Figure 7 It can be seen that the underwater oil contact angle of the alumina ceramic membrane without adding silica prepared in Comparative Example 1 is less than 140°, and it does not reach super oleophobicity (underwater oil contact angle greater than 150°), while the alumina ceramic membranes with added silica all show super oleophobicity.
[0065] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing an underwater super oleophobic alumina ceramic microfiltration membrane, characterized in that: include: (1) ball-milling nano-alumina, nano-silicon dioxide and water to obtain a powder dispersion; (2) adding a binder and a pore-forming agent to the powder dispersion for secondary ball milling, fully mixing, drying, and sieving to obtain a pre-pressed powder; (3) placing the pre-pressed powder in a mold and pressing it into shape to obtain a ceramic green body membrane; (4) Sintering the ceramic green body membrane to obtain an underwater super oleophobic alumina ceramic microfiltration membrane.
2. The method for preparing according to claim 1, characterized in that: (1) The particle size of the nano-alumina is 150-300 nm, and the particle size of the nano-silicon dioxide is 30-200 nm; the molar ratio of the nano-alumina to the nano-silicon dioxide is 1:0.05-3.
3. The method for preparing according to claim 1, characterized in that: (1) The ball milling time is 12 to 48 hours.
4. The method for preparing according to claim 1, characterized in that: (2) The binder is a mixture of one or more of methyl cellulose, carboxymethyl cellulose and polyvinyl alcohol; the amount of the binder added is 1 to 20% of the mass of the powder dispersion.
5. The method for preparing according to claim 1, characterized in that: (2) The medium pore-forming agent is a mixture of one or more of corn starch, calcium carbonate, and yellow dextrin; the amount of the pore-forming agent added is 5 to 70% of the mass of the powder dispersion.
6. The method for preparing according to claim 1, characterized in that: (3) The pressure of the medium pressing molding is 5 to 60 MPa.
7. The method for preparing according to claim 1, characterized in that: The thickness of the ceramic green body membrane obtained in (3) is 0.5 to 2.5 mm.
8. The method for preparing according to claim 1, characterized in that: (4) The sintering conditions are as follows: the temperature is raised from room temperature to 200°C at a rate of 0.5-5°C / min, kept at that temperature for 0.5-3h, then raised to 800°C at a rate of 0.5-15°C / min, kept at that temperature for 0.5-3h, and finally raised to 1100-1600°C at a rate of 0.5-15°C / min, kept at that temperature for 0.5-10h.
9. An underwater super oleophobic alumina ceramic microfiltration membrane prepared by the method according to any one of claims 1 to 8.
10. An application of the underwater super oleophobic alumina ceramic microfiltration membrane according to claim 9, characterized in that: Used in the fields of oil-water separation, wastewater treatment and drinking water treatment technology.
Citation Information
Patent Citations
Super-hydrophobic oleophylic composite ceramic membrane preparation method
CN104945016A
Ultrathin aluminum oxide ceramic substrate with submicrometer structure and preparation method
CN108947504A
Ceramic composition, microfiltration ceramic membrane as well as preparation method and application of microfiltration ceramic membrane
CN115557778A
Ceramic membrane for oil-water separation and preparation method thereof
CN116283238A
Ceramic oil-water separation membrane and preparation method thereof
CN117839437A